2012 IEEE 8th International Conference on Wireless and Mobile Computing, Networking and Communications (WiMob) 2012
DOI: 10.1109/wimob.2012.6379153
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and coding region of interests in bi-level images for data reduction in Wireless Visual Sensor Network

Abstract: Abstract-Wireless Visual Sensor Network (WVSN) is formed by deploying many Visual Sensor Nodes (VSNs) in the field. The VSNs acquire images of the area of interest in the field, perform some local processing on these images and transmit the results using an embedded wireless transceiver. The energy consumption on transmitting the results wirelessly is correlated with the information amount that is being transmitted. The images acquired by the VSNs contain huge amount of data due to many kinds of redundancies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 11 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…In 9 , we explored the compression efficiency of Region of Interest (ROI) coding for various geometrical shaped objects in the black images. The results of ROI coding in 9 showed some improvement in the compression efficiency compared to that of change coding in 8 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In 9 , we explored the compression efficiency of Region of Interest (ROI) coding for various geometrical shaped objects in the black images. The results of ROI coding in 9 showed some improvement in the compression efficiency compared to that of change coding in 8 .…”
Section: Introductionmentioning
confidence: 92%
“…We investigated the possibility of further data reduction based on, change coding and ROI coding in 8,9 respectively. We concluded in 8 that change coding provides better compression efficiency than image coding for up to 95 % changes in terms of number of objects in the adjacent frames.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored the possibility of further data reduction in [11] based on change coding, where we concluded that change coding is better than image coding (the image coding is investigated in [7]) for up to 95% changes in terms of number of objects in the neighbouring frames. We explored the compression efficiency of Region of Interest (ROI) coding for various geometrical shaped objects in the black images and presented the results in [12]. The results of ROI coding in [12] showed some improvements in the compression performance compared to the results of change coding in [11].…”
mentioning
confidence: 99%
“…We explored the compression efficiency of Region of Interest (ROI) coding for various geometrical shaped objects in the black images and presented the results in [12]. The results of ROI coding in [12] showed some improvements in the compression performance compared to the results of change coding in [11].…”
mentioning
confidence: 99%